Reflexiones sobre densidad urbana y centralidades en la metrópoli de Lima, siglo XXI - Fernández de Córdova, Graciela (2015)
This research proposes to study centralities based on how they relate to urban density. It starts with Lima’s urban process, where there are four important plans. The ?rst plan guided expansion beyond the walls of the city. The second one constituted a single traditional metropolitan centrality. The third one lowered urban density by extending urban limits. Finally, the fourth one proposes a conceptual scheme to integrate large expansion areas through comprehensive service centers, thus marking an urban structure with a single large centrality and different agglomerations of houses that are dispersed as they expand in the periphery. In the last decade, there has been a consolidation of a continuous territory that is still functionally dispersed in terms of its equipment and morphology. Within the framework of urban compactness, we propose a methodological approach to create integration centralities. The analysis considers urban scales oriented towards the study of urban restructuring, the center’s functional and spatial articulation – in relation to other surrounding centers and areas – and the habitability of public space as support for everyday activities in these centers. This study contributes to the identi?cation of features needed to create integration centralities.